Traumatic rectal injuries: Is the combination of computed tomography and rigid proctoscopy sufficient?. Issue 6 (December 2018) - Trust, Marc D.; Veith, Jacob; Brown, Carlos V.R.; Sharpe, John P.; Musonza, Tashinga; Holcomb, John; Bui, Eric; Bruns, Brandon; Andrew Hopper, H.; Truitt, Michael; Burlew, Clay; Schellenberg, Morgan; et al.
Abstract : BACKGROUND: There are no clear guidelines for the best test or combination of tests to identify traumatic rectal injuries. We hypothesize that computed tomography (CT) and rigid proctoscopy (RP) will identify all injuries. METHODS: American Association for the Surgery of Trauma multi-institutional retrospective study (2004–2015) of patients who sustained a traumatic rectal injury. Patients with known rectal injuries who underwent both CT and RP as part of their diagnostic workup were included. Only patients with full thickness injuries (American Association for the Surgery of Trauma grade II-V) were included. Computed tomography findings of rectal injury, perirectal stranding, or rectal wall thickening and RP findings of blood, mucosal abnormalities, or laceration were considered positive. RESULTS: One hundred six patients were identified. Mean age was 32 years, 85(79%) were male, and 67(63%) involved penetrating mechanisms. A total of 36 (34%) and 100 (94%) patients had positive CT and RP findings, respectively. Only 3 (3%) patients had both a negative CT and negative RP. On further review, each of these three patients had intraperitoneal injuries and had indirect evidence of rectal injury on CT scan including pneumoperitoneum or sacral fracture. CONCLUSION: As stand-alone tests, neither CT nor RP can adequately identify traumatic rectal injuries. However, the combination of both test demonstrates a sensitivity of 97%. Intraperitoneal injuries may be missed by both CT and RP, so patients with a high index of suspicion and/or indirect evidence of rectal injury on CT scan may necessitate laparotomy for definitive diagnosis. LEVEL OF EVIDENCE: Diagnostic, level IV.